"I Am What I Am Not Yet": A Progress Report on the Study of the Learning Journeys of the First Modern Teaching Artists. Issue 1 (2nd January 2016) - Gawlowski Pratt, Melissa
ABSTRACT: This in-process study investigates experiences of Lincoln Center's first teaching artists, connecting their work in the 1970s to contemporary practice.